Malaysian dental graduates' competence in holistic care: what do graduates and employers think? - Yusof, Z.Y.M.; Jaafar, Nasruddin; Jallaludin, R.L.R.; Abu-Hassan, M.I.; Razak, I.A. (American Dental Education Association, 2010)
The purpose of this study was to explore the University of Malaya (UM) dental graduates' competence in holistic care in real settings from the employers' and graduates' perspectives A self-administered questionnaire consisting of ten domains was sent to thirty senior dental officers of the Ministry of Health (MOH) and 164 UM graduates In this article, nineteen major competencies that best represent the graduates' competence in the provision of holistic care are discussed Each competency was rated on a scale of 1 (very poor) to 4 (very good) and was categorized as "poor and of major concern" (if less than 60 percent of respondents scored good or very good), "satisfactory and of minor concern" (60-69 percent), or "excellent" (70 percent and above) One hundred and six out of 164 graduates (64 6 percent) and twenty-nine out of thirty employers (96 7 percent) responded Overall, the employers rated the graduates lower than what the graduates rated themselves on all items While the graduates felt they were excellent and satisfactory in sixteen out of nineteen items (84 2 percent), the employers felt they were poor in fourteen out of nineteen (73 7 percent) Both groups agreed that the graduates were excellent in communication, but poor in life-saving skills, obtaining patient's family and psychosocial histories, and recognizing signs and symptoms (not intraoral) indicating the presence of a systemic disease In conclusion, although the graduates felt competent in the majority of the holistic care competencies, the employers had some reservations over such claims Outcomes of the study led to recommendations to Incorporate longer community-based learning hours, an improved behavioral science component, a module for special care patients, and multide-partmental collaborative teachings in the new integrated program aimed for implementation in 2011.